2016
DOI: 10.1111/2041-210x.12581
|View full text |Cite
|
Sign up to set email alerts
|

Data reliability in citizen science: learning curve and the effects of training method, volunteer background and experience on identification accuracy of insects visiting ivy flowers

Abstract: 210X.12581Abstract  Citizen science, the involvement of volunteers in collecting of scientific data, can be a useful research tool. However, data collected by volunteers are often of lower quality than that collected by professional scientists. We studied the accuracy with which volunteers identified insects visiting ivy (Hedera) flowers in Sussex, England. In the first experiment, we examined the effects of training method, volunteer background and prior experience. Fifty-three participants were trained for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
83
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 43 publications
4
83
0
2
Order By: Relevance
“…However, with training, citizen scientists can collect useful and accurate pollinator information Deguines et al 2012). Methods such as expert verification of volunteer-collected arthropod specimens (Gardiner et al 2012), hands-on training Ratnieks et al 2016), and/or assigning target species to groups based on color or pattern (Roy et al 2016) all reduce, although do not always eliminate, volunteer errors.…”
Section: Discussionmentioning
confidence: 99%
“…However, with training, citizen scientists can collect useful and accurate pollinator information Deguines et al 2012). Methods such as expert verification of volunteer-collected arthropod specimens (Gardiner et al 2012), hands-on training Ratnieks et al 2016), and/or assigning target species to groups based on color or pattern (Roy et al 2016) all reduce, although do not always eliminate, volunteer errors.…”
Section: Discussionmentioning
confidence: 99%
“…Questo dato è in accordo con Gardiner et al (2012) che rilevano come la CS applicata al monitoraggio delle coccinelle fornisce dati corretti nell'81-100% dei casi; Ratnieks et al (2016) hanno accertato che i volontari identificano correttamente fino al 94% di specie di insetti. Questi due autori hanno anche dimostrato come i metodi e i materiali impiegati per l'addestramento e il trasferimento di informazioni ai volontari abbiano avuto un ruolo determinante nell'accuratezza delle identificazioni.…”
Section: Discussioneunclassified
“…Although professionally collected data are the preferred data source for SDM, they are expensive to collect and are often in short supply. Data collected using proper crowdsourcing techniques, often termed "opportunistic data" [3][4][5][6][7][8][9][10][11][12] or unstructured volunteer data, can provide ecologists with a variety of biodiversity monitoring data. Consequently, volunteer-based citizen science monitoring systems have attracted a lot of attention.…”
Section: Introductionmentioning
confidence: 99%
“…Munson et al [27] also found that the eBird opportunistic data had more uncertainty than the professionally collected North American Breeding Bird Survey (BBS) data. Due to these and other issues, many still consider opportunistic data to be low quality and unreliable for research and conservation planning purposes [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation